ESRA19-0374 Combined spinal epidural anesthesia for emergency cesarean section in a clinically severe obese parturient with dilated cardiomyopathy. (30th August 2019) - Luy, J; Lim, L
Abstract : Background and aims: A 27-year-old, 38 weeks AOG, clinically severe obese female weighing 112 kg, height 148 cm (BMI 51.1) primigravida, 2D echo result of ejection fraction 12%, dilated left ventricle, severe global hypokinesia grade 3 diastolic dysfunction, dilated RV with hypokinetic wall, underwent emergency cesarean section (CS) due to arrest in cervical dilatation. Methods: The risks of CS and anesthetic management were fully disclosed to the patient. She consented to a combined spinal-epidural technique. Patient was placed in sitting position and single needle technique was done. Only during third attempt was the epidural space finally attained. Only 5 mg Bupivacaine heavy was instilled in the subarachnoid space and 7 ml of Ropivacaine 0.75% given incrementally to reach T7. Results: The patient remained stable hemodynamically: A total of 700 ml of lactated Ringer's solution was administered. Estimated blood loss about 300cc, urine output about 200cc. The procedure lasted about 1.5 hours. Patient was handed over to PACU with postoperative epidural ropivacaine drip and morphine running at 10 cc/hr. Postoperatively, the patient was pain-free, comfortable and did not require any postoperative analgesics. Both mother and baby were discharged well after three days. Conclusions: Patient's cardiac disease will be affected by the physiologic changes associated with pregnancy, obesity and the chosen anesthetic management. Therefore, the low-dose sequential combined spinal epidural is a safe option for the clinically severe obese parturient with dilated cardiomyopathy because it provides effective analgesia and anesthesia while maintaining hemodynamic stability.